Mt-Keima detects PINK1-PRKN mitophagy in vivo with greater sensitivity than mito-QC. Issue 11 (2nd November 2021) - Liu, Yi-Ting; Sliter, Danielle A.; Shammas, Mario K.; Huang, Xiaoping; Wang, Chunxin; Calvelli, Hannah; Maric, Dragan S.; Narendra, Derek P.
ABSTRACT: PINK1 and PRKN, which cause Parkinson disease when mutated, form a quality control mitophagy pathway that is well-characterized in cultured cells. The extent to which the PINK1-PRKN pathway contributes to mitophagy in vivo, however, is controversial. This is due in large part to conflicting results from studies using one of two mitophagy reporters: mt-Keima or mito-QC. Studies using mt-Keima have generally detected PINK1-PRKN mitophagy in vivo, whereas those using mito-QC generally have not. Here, we directly compared the performance of mito-QC and mt-Keima in cell culture and in mice subjected to a PINK1-PRKN activating stress. We found that mito-QC was less sensitive than mt-Keima for mitophagy, and that this difference was more pronounced for PINK1-PRKN mitophagy. These findings suggest that mito-QC's poor sensitivity may account for conflicting reports of PINK1-PRKN mitophagy in vivo and caution against using mito-QC as a reporter for PINK1-PRKN mitophagy. Abbreviations: DFP: deferiprone; EE: exhaustive exercise; FBS: fetal bovine serum; OAQ: oligomycin, antimycin, and Q-VD-OPH; OMM: outer mitochondrial membrane; PBS: phosphate-buffered saline; PD: Parkinson disease; UPS: ubiquitin-proteasome system.